New RER stations for Brussels? Challenges, methods and constraints - Kevin Lebrun; Frédéric Dobruszkes (Brussels Studies)
This article goes back over the debate which still remains to be settled and which divides the Brussels-Capital Region and the SNCB regarding the creation of new urban railway stations in the framework of the RER project. Our aim is to provide an objective (or at least methodologically transparent and clearly presented) assessment which is up to date as regards the relevance of these stations. Thus, after presenting the problem and discussing possible methods, we propose a calculation of the potential of each of the stations proposed by the different urban planning documents of the Brussels Region.We thus illustrate the pertinence of most of them, a significant share of which are more relevant than some of the existing secondary stations in Brussels. However, the most promising stations are often those which seem the most difficult from a technical point of view. Conversely, new stations that would be the easiest to build often have the lower traffic potential.Beyond the impartiality of the results, we also insist on the fact that the decision to put a station (back) into service depends above all on political action, which reflects the fact that challenges of various dimensions and natures have been taken into account. This is illustrated in our case studies.